PEMBELAJARAN SISTEM HIDROLIK DAN PNEUMATIK DENGAN MENGGUNAKAN AUTOMATION STUDIO - Adi Dewanto; Dessy Irmawati (Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
ABSTRACTStudents find it difficult to master the hydraulic and pneumatic system due to the lack of imagination on the component movement. It affects students’ learningprocess on the hydraulic and pneumatic system application. In order to solve the problem, the lecturer of Mechatronics course used the Automation Studio application. This software was helpful to design various automations, such as combination of hydraulic system, pneumatic system, electric system, and PLC. The lecturing process and design simulation were conducted by using Automation Studio. In general, the students were so much helped by this program in mastering the theory and practice of hydraulic and Pneumatic. On the other hand, it was found some problem in applying the Automation Studio on the classroom. The problems were limited onthe menu option as well ason the technical aspects related to the number of the computer. The implications from the writers’ experience in using Automation Studio were there was an opportunity for computer programmer to create learningmedia/ software for certain competence which was relevant, accessible and applicable. Also, in case of software preparation, it should be conducted by the lecturers and the students before the learning process.Keywords: automation studio program, learning process, Pneumatic and hydraulic learning